Sistem Pendukung Keputusan Penentuan Jenis Kulit Terbaik Untuk Pembuatan Sepatu Dengan Menggunakan Metode VIKOR - Betrik Juliana Hutapea; Mentari Ananda Hasmi; Abdul Karim; Suginam Suginam (STMIK Budi Darma, 2018)
Shoes are equipment of body parts that serve to protect the soles of the feet from heat, sharp objects, and dirt. Shoes are also part of the fashion. There are hundreds of shoe types, which are divided into the function, model, material, size, origin, and so on. For example office shoes, boots, sneakers, snickers, sports shoes, party shoes, leather shoes, high heels and hundreds more. In general, shoe parts (shoe construction) are divided into two parts, namely upper and bottom. In the bottom (bottom) usually made of rubber or wood, while the top there is made of fabric, leather, imitation materials or other synthetic fibers. Decision Support System is a computerized system and designed to increase the effectiveness of decision making to solve problems that are semi-structured and unstructured so that in the process of making decisions can be more qualified. This application will be made is an application that guided by VIKOR method. Therefore, applications based on VIKOR method is considered suitable for calculating the best skin types for shoemaking.